Improving physical activity among adolescents through multisectoral actions: World Health Organization - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2020)
Insufficient physical activity has been regarded as one among the potential risk factors for the development of non-communicable diseases and the associated complications, including mortality. The World Health Organization has recommended for at least 60 minutes of physical activity per day for adolescents. In the global mission to improve the levels of physical activity and to reduce the percentage of insufficient physical activity by 10% by 2025, there is an immense need to formulate effective strategies and programs for the benefit of adolescents. At the same time, it is extremely important to implement multi-sectoral actions, which will then offer varied chances for adolescents and youths to be physically active. In conclusion, physical activity is an important aspect to ensure optimal health and wellbeing in all age-groups. It is the need of the hour that nations and communities should implement measures to enhance the number of opportunities available for adolescents to be physically active.